Systematic Literature Review (SLR): Analisis Upaya Guru dalam Mengatasi Kesulitan Belajar Peserta Didik di Sekolah Dasar - Nisa, Sahrun; Arumdati, Arumdati (Lembaga Yasin AlSys, 2024)
Throughout the educational process at school, both teachers and students should strive to achieve the best results during the teaching and learning process. Teachers certainly hope that all students succeed in their learning and obtain satisfactory learning results according to expectations. “However, in fact, many students do not get the expected learning results due to difficulties in the learning process. Difficulties during the learning process faced by students are not a new thing for teachers. However, this problem still cannot be underestimated because it has a bad impact on students, teachers, and even schools. This learning difficulty is influenced by internal factors that come from the students themselves and external factors that come from outside the students. Thus, this study was conducted with the aim of analyzing teachers' efforts in overcoming students' learning difficulties, especially at the elementary school level. This type of research is in the form of a literature study”. The data collection technique is carried out by identifying discourses sourced from books, papers, and articles related to